Implementasi Manajemen Peserta Didik dalam Upaya Meningkatkan Kedisiplinan Siswi di Mts Assa’adah II - Nur Faizah, Dwi Intan; Choiruddin , Muhammad; Anwar, Farikhul (Jurnal Studi Multidisiplin Qomaruna, 2025)
Student management is a systematic effort undertaken by educational institutions to manage student development from admission to graduation through the stages of planning, implementation, and evaluation. In the context of Islamic education, student management plays a strategic role in shaping character and discipline through the internalization of religious values. This study aims to analyze the implementation of student management in improving the discipline of female students at MTs Assa’adah II, Gresik. This study employs a qualitative approach with a case study design. Data were collected through in-depth interviews, participatory observation, and document analysis involving stakeholders directly engaged in student development. Data analysis was conducted using the Miles and Huberman model, which consists of data reduction, data display, and conclusion drawing. The findings indicate that student management at MTs Assa’adah II is implemented in a structured and integrated manner through the planning of religious habituation programs, the application of a violation point system accompanied by rewards and punishments, and continuous discipline evaluation. The integration of religious habituation with behavioral reinforcement mechanisms was found to foster disciplinary awareness among female students that goes beyond mere compliance with rules and develops into self-regulation. This study concludes that student management based on Islamic values effectively enhances student discipline and has the potential to serve as a practical reference for other madrasas in strengthening character education.